“Children Of The Same History”: Memories Of Politics And Demand For Justice In H.i.j.o.s. Rosario - Cinto, Agustina (Instituto de Altos Estudios Sociales, 2021)
This paper analyzes the memories of politics developed by H.I.J.O.S. Rosario and the relation with its practices of demand for justice, specifically, the escraches and the participation in trials for crimes against humanity. Whereas the escraches are closely related to the memories of the politics supported by the organization, participation in the trials put a strain on those memories, in particular, the representation of peoplewho were detained or disappeared. H.I.J.O.S. Rosario, as part of the local human rights movement, establishes ruptures and continuities regarding the preceding organizations, in relation to the notion of memory, but also modes of political organization and participation. Considering the generational position of H.I.J.O.S., the slogan “We all are children of the same history” synthesizes some of these ruptures and continuities. Fieldwork for this ethnographic research was developed between 2009 and 2016, and consists of open-ended interviews, participant observation, and documentary analysis of the H.I.J.O.S. productions and newspaper articles.